AUDIT MANAJEMEN SEKTOR PUBLIK: EVALUASI ASPEK VALUE FOR MONEY ATAS KINERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA AMBON - Dirk Berly Tehuayo (P3M Politeknik Negeri Ambon, 2023)
This study aims to test the reliability of management audits as a strategic instrument for evaluating and improving the effectiveness, efficiency, and economy (3E) of public services at the Population and Civil Registration Office (Disdukcapil) in Ambon City. The research was motivated by widespread complaints from Ambon residents regarding the slow issuance of documents due to technical system constraints and limited staffing. Using descriptive qualitative methods supported by literature review (secondary data analysis from previous journals) and a comparison of normative criteria, this study describes how management audits address the root causes of regional bureaucratic operational problems. The literature analysis indicates that the ineffectiveness of services at Disdukcapil in Ambon City stems from the region's unique fiscal capacity as an archipelagic region, weak digital infrastructure mitigation (network errors), and suboptimal staffing ratios. The management audit provides recommendations for integrating a one-stop shop system and delaying verification desks. In conclusion, periodically strengthening the internal audit function by the Ambon City Inspectorate is crucial in transforming public complaints into accountable governance improvements. Keywords: Management Audit, Public Sector, Ambon City, Value for Money, Public Service.